Between threads, aesthetics, and the popular, animating a puppet.: Reflections about the creation of puppets and puppet theater in a class at the Instituto Popular de Cultura-Cali. (The Voz a Vos Bulletin, 2023)
The look of the puppet as an object that is moved by another, is something very simple in the relationship of the puppet theater from a broader aesthetic conception. This article is part of the Central Workshop 2 class, whose objective is to generate a laboratory process around the puppets. In this case, for two years, different observations were made by the teacher and a student (now graduated) about the class, the creation of the puppet, and a puppet play. The objective pursued is to capture three aspects of said observation, on the one hand, the relationship of the popular, as the foundation of the Popular Institute of Culture, the aesthetics, and the postulates of the class, fundamentally centered on the puppet. In this way, a final result is not sought, but rather it is the sum of what is observed, with the two analysis measures, going through a search for what is called the subject. This opens the possibility of continuing this analysis and subsequent looks, more toward the creation of the work and the role of the puppet in other artistic constructions.